A Novel Single-Phase Shunt Active Power Filter with a Cost Function Based Model Predictive Current Control Technique - Belqasem Aljafari; Kanagavel Rameshkumar; Vairavasundaram Indragandhi; Selvamathi Ramachandran (Energies, 2022)
For a single-phase Shunt Active Power Filter (SAPF) with a two-step prediction, this research presents a modified current control based on a Model Predictive Current Control (MPCC) technique. An H-bridge inverter, a DC link capacitor, and a filter inductor comprise the single-phase SAPF topology. The SAPF reference current is computed using the DC-link capacitor voltage regulation-based PI control technique. The weighting factor-based model predictive current controller is used to track the current commands. The essential dynamic index for evaluating waveform quality is the Total Harmonic Distortion (THD) of a source current and switching frequency of power switches. The conventional methods the THD and switching frequency are not considered as an objective function, so that a weighting factor-based MPCC technique is used to obtain a good compromise between the THD of the source current and switching frequency of power switches. Through MATLAB simulation and experimentation with the Cyclone-IV EP4CE30F484 FPGA board, the usefulness of the proposed control technique is proven. As compared with hysteresis, predictive PWM, and conventional MPCC control methods, the cost function-based MPCC algorithm provides a lower switching frequency (13.4 kHz) with an optimal source current THD value.